Pengaruh Kualitas Produk, Citra Merek, dan Persepsi Harga Terhadap Keputusan Pembelian Pada Richeese Factory - Faeza, Violina; NS, Bambang (Innovative: Journal Of Social Science Research, 2024)
The purpose of this study is to determine the influence of product quality, brand image and perceived price of Richeese Factory products on purchasing decisions, by applying quantitative methods and accidental sampling at Richeese Factory. The research results show a value of 4.104 with a significance of 0.000. With a significance of less than 0.05, H0 is rejected, indicating that product quality has a partial effect on purchasing decisions at Richeese Factory. Brand image with a calculated t value of 1.665 and a significance of 0.001. This states that brand image also partially influences purchasing decisions at Richeese Factory. The t-calculated results for price perception produce a value of 6.116 with a significance of 0.000. With a significance of less than 0.05, H0 is rejected, indicating that price perceptions have a partial effect on purchasing decisions.